2023
DOI: 10.1017/s0029665123002707
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining an ageing population: the role of micronutrients in frailty and cognitive impairment

Abstract: Age-related frailty and cognitive decline are complex multidimensional conditions that significantly impact the ability of older adults to sustain functional capacity and independence. While underlying causes remain poorly understood, nutrition continually emerges as one associated risk element. Many studies have addressed the importance of adequate nutrition in delaying the onset of these conditions, but the specific role of micronutrients is not well established. The consideration of pre-frailty as an outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 179 publications
0
8
0
Order By: Relevance
“…Vicente et al (2020) suggested that more inflammatory diets could lead to higher chances of being frail/pre-frail. In another review, O’Connor et al, (2023) suggested that micronutrients B12 and folate, vitamin B12 and folate; vitamin D; carotenoids, lutein and zeaxanthin were all important, but most of the consituent studies reviewed examined PF or CI, not CF. Khalid et al, (2022) however, specifically associated Beta-cryptoxanthin and zeaxanthin with CF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vicente et al (2020) suggested that more inflammatory diets could lead to higher chances of being frail/pre-frail. In another review, O’Connor et al, (2023) suggested that micronutrients B12 and folate, vitamin B12 and folate; vitamin D; carotenoids, lutein and zeaxanthin were all important, but most of the consituent studies reviewed examined PF or CI, not CF. Khalid et al, (2022) however, specifically associated Beta-cryptoxanthin and zeaxanthin with CF.…”
Section: Resultsmentioning
confidence: 99%
“…In another review,O'Connor et al, (2023) suggested that micronutrients B12 and folate, vitamin B12 and folate; vitamin D; carotenoids, lutein and zeaxanthin were all important, but most of the consituent studies reviewed examined PF or…”
mentioning
confidence: 99%
“…Therefore, the concurrence of frailty with stroke elevates the predisposition to nutritional risks. Elevated nutritional risks might exacerbate age-associated muscle atrophy and diminished strength, potentially leading to functional incapacitation, mood disorders, falls, compromised immune response, and cognitive impairments, thereby intensifying frailty [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition refers to a condition characterized by an inadequate intake of nutrients, an imbalance of vital nutrients, or an impaired ability to utilize nutrients effectively [ 25 ]. Insufficient intake of essential nutrients can give rise to various health problems, such as weakness, fatigue, and an increased risk of cognitive decline and dementia in older individuals [ 7 , 26 ]. Furthermore, malnutrition can lead to chronic inflammation, which in turn can cause damage to brain cells, impair cognitive function, and contribute to cognitive frailty [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient intake of essential nutrients can give rise to various health problems, such as weakness, fatigue, and an increased risk of cognitive decline and dementia in older individuals [ 7 , 26 ]. Furthermore, malnutrition can lead to chronic inflammation, which in turn can cause damage to brain cells, impair cognitive function, and contribute to cognitive frailty [ 26 , 27 ]. However, studies on the association between malnutrition and cognitive frailty in community-dwelling elderly are limited.…”
Section: Introductionmentioning
confidence: 99%